Awakening Solar Water‐Splitting Activity of ZnFe2O4 Nanorods by Hybrid Microwave Annealing. Issue 6 (2nd December 2014) - Kim, Ju Hun; Kim, Jin Hyun; Jang, Ji‐Wook; Kim, Jae Young; Choi, Sun Hee; Magesh, Ganesan; Lee, Jinwoo; Lee, Jae Sung
<x xml:space="preserve">Abstract</x> 1D zinc ferrite (ZnFe2O4) photoanode is fabricated on an F‐doped tin oxide substrate at a low temperature by an all‐solution method. To activate the material for photoelectrochemical water splitting, the hybrid microwave annealing (HMA) is applied with graphite powder as a susceptor. Thus, HMA treatment of ZnFe2O4 photoanode synthesized at 550 °C increases the photocurrent density of water oxidation by 15 times. In contrast, the conventional thermal annealing at 800 °C brings only 1.7‐fold increase. The various physical characterizations and hole scavenger photooxidation experiments with H2O2 reveal that the post‐HMA treatment anneals the surface defect states and enhances the crystallinity. Hence, HMA treatment is effective to suppress charge‐carrier recombination both on the surface and in the bulk of ZnFe2O4 to bring out its latent solar water‐splitting activity.